2020
DOI: 10.1097/md.0000000000023301
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of self-reported chronic urticaria among adults in grasslands of northern China

Abstract: The clinical epidemiological characteristics of chronic urticaria (CU) in different populations were not completely consistent, and the epidemiological characteristics of CU were very complex. At present, there were some patient-based studies on CU, but few natural population-based studied in the world. This study aimed to analysis the prevalence of self-reported CU among adults in grasslands of northern China and its closely related factors. A multistage and proportionately stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…CU was specified as CSU/CIU in 17 studies [9, 24, 29, 31, 33, 34, 39, 42, 43, 45-47, 49-52, 54] and CIndU in 4 studies [18, 20, 27, 53]. Fourteen studies retrieved information on atopic disorders through medical charts/records [20, 21, 23, 27, 30, 32, 33, 35, 38, 42, 43, 50, 52, 53], 8 by questionnaire/self-report [18, 19, 31, 37, 40, 46, 47, 51], 7 by a physician diagnosis [9, 29, 34, 36, 41, 48, 49], and 9 did not describe their source of information [22, 24-26, 28, 39, 44, 45, 54]. All studies, but one, reported point prevalences of atopic disorders in CU, and six studies reported ORs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…CU was specified as CSU/CIU in 17 studies [9, 24, 29, 31, 33, 34, 39, 42, 43, 45-47, 49-52, 54] and CIndU in 4 studies [18, 20, 27, 53]. Fourteen studies retrieved information on atopic disorders through medical charts/records [20, 21, 23, 27, 30, 32, 33, 35, 38, 42, 43, 50, 52, 53], 8 by questionnaire/self-report [18, 19, 31, 37, 40, 46, 47, 51], 7 by a physician diagnosis [9, 29, 34, 36, 41, 48, 49], and 9 did not describe their source of information [22, 24-26, 28, 39, 44, 45, 54]. All studies, but one, reported point prevalences of atopic disorders in CU, and six studies reported ORs.…”
Section: Resultsmentioning
confidence: 99%
“…For adult subjects only, the point prevalence ranged between 2 and 30% and the pooled point prevalence was estimated to 14% (9–21%, I 2 = 95%) (online suppl. S2b) [9, 19, 21, 22, 26, 28, 37, 41, 43, 51]. One study did not provide any quantitative data but found subjects with CU to have a significantly lower risk of a personal history of asthma and rhinitis compared to the general population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations